1993
DOI: 10.1084/jem.177.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Surface expression of alpha 4 integrin by CD4 T cells is required for their entry into brain parenchyma.

Abstract: Summary Cloned CD4 T cell lines that recognize the Ac1-16 peptide of myelin basic protein bound to I-A" were isolated and used to analyze the immunopathogeuesis of experimental autoimmune encephalomyelitis (EAE). T helper type 1 (Thl) clones induced disease, while Th2 clones did not. Using variants of a single cloned Thl line, the surface expression of o~4 integrins (very late antigen 4 [VLA-4]) was identified as a major pathogenic factor. Encephalitogenic clones and nonencephalitogenic variants differ by 10-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
458
1
5

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 779 publications
(476 citation statements)
references
References 65 publications
12
458
1
5
Order By: Relevance
“…Our findings of IL-2 mRNA expression throughout the clinical disease are consistent with previous studies indicating the importance of IL-2 in EAE. IL-2 is known to be present in the CNS in EAE (Baker et al, 1991;Merrill et al, 1992;Renno et al, 1994) and encephalitogenic T cell clones secrete IL-2 (Ando et al, 1989;Baron et al, 1993). Expression of IFN-(relative to -actin) was observed throughout the course of the disease, with a peak on days 17-19, during late clinical recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings of IL-2 mRNA expression throughout the clinical disease are consistent with previous studies indicating the importance of IL-2 in EAE. IL-2 is known to be present in the CNS in EAE (Baker et al, 1991;Merrill et al, 1992;Renno et al, 1994) and encephalitogenic T cell clones secrete IL-2 (Ando et al, 1989;Baron et al, 1993). Expression of IFN-(relative to -actin) was observed throughout the course of the disease, with a peak on days 17-19, during late clinical recovery.…”
Section: Discussionmentioning
confidence: 99%
“…EAE is characterized by infiltration of the nervous system with activated T lymphocytes and macrophages (Raine, 1984;McCombe et al, 1992). Cloned encephalitogenic T cells secrete interleukin-2 (IL-2) and interferon-(IFN-) (Ando et al, 1989;Baron et al, 1993). Thus, encephalitogenic cells are Th1-like cells, as defined by the original concept of Mosmann and Coffman (1989) that CD4 + T cells produce either IL-2 and IFN-(Th1 cells) or IL-4, IL-5 and IL-10 (Th2 cells).…”
Section: Introductionmentioning
confidence: 99%
“…The transient decrease in MBP-reactive or VLA-4 þ cells at 24 h (1 day before clinical symptoms) followed by an increase thereafter is compatible with the hypothesis that activated T cells were recruited into the brain from the cervical lymph node. Baron et al [20] demonstrated that surface expression of VLA-4 was important for CD4 þ T cell entry into brain parenchyma. The VLA-4 integrins may be crucial in allowing activated effector T cells to leave the blood and enter the brain.…”
Section: Discussionmentioning
confidence: 99%
“…After the seminal study by Yednock et al (2) demonstrating that Abs blocking ␣ 4 integrin inhibit EAE by blocking T cell interaction with the BBB, numerous following studies confirmed and extended the predominant involvement of ␣ 4 integrin/VCAM-1 in inflammatory cell recruitment into the CNS in different EAE models in a number of species (3)(4)(5)(6). Using intravital microscopy, we have demonstrated that the recruitment of encephalitogenic T cell blasts across the spinal cord white matter microvasculature in healthy mice depends on ␣ 4 integrin-mediated initial capture and G protein-dependent arrest (7).…”
mentioning
confidence: 97%
“…I n multiple sclerosis (MS), 3 and in its animal model, experimental autoimmune encephalomyelitis (EAE), circulating immune cells gain access to the CNS and cause inflammation, blood-brain barrier (BBB) breakdown, and demyelination, which all set the stage for the development of the clinical manifestations of this disabling disease. EAE is a T cell-mediated autoimmune disease, which can be induced either by immunization with myelin Ags or by the transfer of encephalitogenic T cells in susceptible rodent strains including mice.…”
mentioning
confidence: 99%